A Rare Tumor in a Patient with Hepatic Hydatic Cyst: Adrenal Hepatoid Adenocarcinoma - Fatma Umit Malya; Suleyman Bozkurt; Mustafa Hasbahceci; Gokhan Cipe; Issam Cheikh Ahmad; Zuhal Gucin; Oguzhan Karatepe; Mahmut Muslumanoglu (Case Reports in Medicine)
Hepatoid adenocarcinoma (HAC) is a very rare type of extrahepatic adenocarcinoma which has a clinicopathologic and morphologic similarity to hepatocellular carcinoma (HCC). Although it is not common, it can be seen in organs other than the liver. The correct diagnosis can be a challenge because of its clinically similarity to HCC and the diagnosis is usually achieved by pathological examination following the surgery. We present a 48-year-old woman who was following with the diagnosis of stage 5 hepatic hydatic cyst. In her routine blood examinations, her alpha feta protein level was found higher than normal and her abdominal computed tomography and magnetic resonance findings did not reveal any pathological findings rather than hepatic hydatic cysts. There was a high activity of FDG on PET CT in the hepatic region so we performed a right lateral hepatectomy to the patient and final pathology was adrenal hepatoid adenocarcinoma. In this paper we aimed to present a rare case of hepatoid carcinoma of the adrenal gland.